Effect of Type of Cleft and Speech Stimuli on Speech Intelligibility in Individuals with Cleft Lip and Palate - Gnanavel K; Pushpavathi M (Journal of All India Institute of Speech and Hearing, 2020)
Speech intelligibility is the match between the intention of the speaker and the perception of the listener. Intelligibility involves a number of factors, including listener and context variables as well as speaker variables. The objective of the present study is to compare the effect of type of stimuli and type of cleft on perceptual rating of speech intelligibility in individuals with cleft lip and palate. The subjects consisted of 20 individuals with cleft lip and palate who were further divided based on the type of cleft [Repaired cleft lip and palate (5), repaired cleft palate (5), repaired submucous cleft palate (5), unrepaired cleft palate (5)]. The stimuli consisted of 10 words and 10 sentences (oral and nasal sentences) loaded with pressure consonants. The subjects were asked to repeat the stimuli after the investigator. The responses were recorded and subjected to perceptual assessment using a five point speech intelligibility rating scale (Roy, 2000). The perceptual evaluation was done by four speech language pathologists. The results revealed no significant difference in Kruskal Wallis test across types of cleft and type of stimuli (for words, H3 = 1.94, P = 0.58 & for sentences, H3 = 3.379, P=0.33). High inter judge reliability was found between four judges at 0.05 levels of significance on Pearson’s correlation coefficient. Cronbach’s alpha (α) was calculated for words (α =0.836, P < 0.01) and sentences (α =0.819, P, 0.01).These higher alpha values showed higher inter judge reliability (higher internal consistency) among the four judges. Speech intelligibility can be improved by giving speech therapy even after surgery and it is required to eliminate any compensatory articulation productions developed prior to management.